Navigation conditions at the Kama river reach between the Wotkinsk and Nizhny-Kama dams (Russia) (Geography and Tourism, 2013)
A system of reservoirs arranged into a cascade provides conditions favourable for navigation. It is  important, however, that the cascade remains uninterrupted, i.e. that the backwater of the lower located reservoir reaches the dam located above. In the cascade system of the Kama river there is a reach, which has not been elevated due to the fact that the lower located reservoir had not been filled enough to reach the planned level. The free-flowing reach is 150 km long and exemplifies complex fluvial processes. Below the Wotkinsk dam, intensive erosion occurs with an average rate of 9 cm a year. There is a reach that stretches 57-80 km below the dam, where water elevation fluctuates in relation to the water level in the lower located Nizhny-Kama reservoir. It is within this reach that bed load is accumulated, thickness of which has reached 0.8 m. In order to maintain the depth allowing for navigation (3.3 m), intensive dredging must be carried out. Moreover, fluctuation of water levels at both dams in winter season causes ice drifting and jams, which further add to the bed load accumulated.